Why do managers of small and medium-sized businesses seek voluntary Living Wage accreditation? – an exploration of choice rationales. Issue 6 (2nd November 2021) - Werner, Andrea
ABSTRACT: This article explores empirically the choice rationales for voluntary adoption of the Living Wage (LW) by managers of small and medium-sized enterprises (SMEs) in the UK. Framed analytically by related concerns within the fields of employment relations/HRM in SMEs, business ethics and signalling, interviews with owners/directors from 23 SMEs identified a four-fold typology of choice rationales for the LW as: an expression of care for employees, the basis for a high quality service business model, a marker of corporate social responsibility, and a signal to challenge the practice of other economic actors. Opportunities and barriers for voluntary adoption of the LW in SMEs are considered, in addition to their economic effects. The practical implications for LW movements and SME managers are drawn out, and avenues for further research identified.